2022
DOI: 10.1111/are.15796
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dietary supplementation based on essential oils on the quality of gilthead seabream

Abstract: The effectiveness of using essential oils against fish parasites and pathogenic bacteria as environmentally friendly phytotherapeutic agents in the aquaculture industry is demonstrated. A commercial additive composed of garlic essential oil, thymol and carvacrol (AROTEC‐G®) was added to a diet for gilthead seabream (Sparus aurata) as a protection strategy against Sparicotyle chrysophrii. The intense aromatic properties of these essential oils might lead to the need of a suppression time to reverse possible cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In addition, the dietary essential oils generally improve the meat quality and fatty acid composition of fish (Iniesta et al, 2022;Montanher et al, 2016). As Iniesta et al (2022) reported, dietary essential oils improved the textural properties such as hardness in gilthead seabream. Moreover, Montanher et al (2016) stated that the addition of chia oil to the diet of Nile tilapia increased the n − 3 PUFA, especially the alpha-linolenic acid, which showed a sixfold increase.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In addition, the dietary essential oils generally improve the meat quality and fatty acid composition of fish (Iniesta et al, 2022;Montanher et al, 2016). As Iniesta et al (2022) reported, dietary essential oils improved the textural properties such as hardness in gilthead seabream. Moreover, Montanher et al (2016) stated that the addition of chia oil to the diet of Nile tilapia increased the n − 3 PUFA, especially the alpha-linolenic acid, which showed a sixfold increase.…”
Section: Introductionmentioning
confidence: 80%
“…As Iniesta et al. (2022) reported, dietary essential oils improved the textural properties such as hardness in gilthead seabream. Moreover, Montanher et al.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Since the administration of essential oils in fish feed might induce off flavours in the final product, testing of the sensory and physicochemical parameters in fillets of the gilthead seabream (fed AROTEC‐G® for 4 weeks) showed that organoleptic traits were not changed and that fillets did not exhibit aromatic or anomalous odour, nor aromatic or anomalous flavour. Physicochemical parameters were slightly altered; AROTEC‐G®‐fed fish were darker in colour, and the fillet textures showed increased hardiness, adhesiveness and gumminess 134 …”
Section: Disease Managementmentioning
confidence: 99%
“…Physicochemical parameters were slightly altered; AROTEC-G ® -fed fish were darker in colour, and the fillet textures showed increased hardiness, adhesiveness and gumminess. 134 Lastly, propyl-propane-thiosulfinate and propyl-propane-thiosulfonate, two organosulfur compounds from onion (Allium cepa), already known for their antioxidant, antimicrobial, antifungal and antiparasitic properties have been tested in vitro and in feed of Sparicotyle-infected gilthead seabream. 135 While the number of parasites significantly decreased in both trials, authors remarked that the degree of efficiency of Allium compounds will depend on the composition of the active ingredients and the dose of inclusion in the feed.…”
Section: Treatments Against Sparicotylosismentioning
confidence: 99%